Artificial intelligence (AI) in agriculture industry: Experience as a visiting scholar in Angers, France / Associate Professor Ts. Dr Abdul Rahman Saili - Saili, Abdul Rahman (Office of the Deputy Vice-Chancellor (Research & Innovation), 2023)
I would like to share my positive experience as a visiting scholar at École supérieure d'agricultures d'Angers. First of all, I would like to say "thank you very much" to my research partner in France, Dr. Soazig Di Bianco, and the team for giving me this great opportunity. Also, my gratitude goes to the Embassy of France in Malaysia for choosing me as one of the four recipients of the Year 2022 Mobility Grant for Academic Staff. The scholarship includes an allowance that covers the living expenses (including housing) and a round-trip plane ticket. I was also blessed with the support from Universiti Teknologi MARA and especially the Rector of UiTM Sarawak, Professor Dato' Dr. Jamil Hamali. I was able to join the postgraduate classroom sessions to observe and become an invited assessor for student presentations regarding smart agriculture practices among French farmers. Apart from academicians, they also invited industry representatives to become the assessors. This session allowed the students to receive feedback from various individuals including academicians and practitioners. Therefore, the students can improve their project whilst relating it to the current market and industry. This was a good contribution to my teaching and learning development, as I was able to emulate the good approach and incorporate it into my teaching practice.